2014
DOI: 10.1038/labinvest.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural stem cell tropism, early immune activation, and choroid plexus pathology following coxsackievirus infection in the neonatal central nervous system

Abstract: Coxsackievirus B3 (CVB3) and lymphocytic choriomeningitis virus (LCMV) are both neurotropic RNA viruses, which can establish a persistent infection and cause meningitis and encephalitis in the neonatal host. Utilizing our neonatal mouse model of infection, we evaluated the consequences of early viral infection upon the host central nervous system (CNS) by comparing CVB3 and LCMV infection. Both viruses expressed high levels of viral protein in the choroid plexus and subventricular zone (SVZ), a region of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…We previously determined that proliferating neural stem and progenitor cells grown in the subventricular zone of the neonatal brain or grown in culture were preferentially targeted by CVB3 [10], [11], [16], [14], [26]. Furthermore, CVB3 reduced the levels of neurogenesis and altered brain development in a neonatal model of viral infection [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously determined that proliferating neural stem and progenitor cells grown in the subventricular zone of the neonatal brain or grown in culture were preferentially targeted by CVB3 [10], [11], [16], [14], [26]. Furthermore, CVB3 reduced the levels of neurogenesis and altered brain development in a neonatal model of viral infection [15].…”
Section: Resultsmentioning
confidence: 99%
“…This model seems to mirror the late consequences of childhood doxorubicin-induced cardiotoxicity observed in humans which manifests in weakening of the myocardium, an attenuation of cardiac pump performance, and progression towards congestive heart failure. Since previous studies described preferential CVB3 infection of progenitor cells in the CNS [10], [11], [15], [16], [26] and bone marrow [17], we investigated the effect of CVB3 on CPCs in the developing heart. We established a mouse model of juvenile CVB3 infection and observed that not only did CVB3 productively infect CPCs, but infection caused a sustained reduction in the CPC pool into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these recombinant viral constructs have proven to be quite stable, although the loss of the foreign insert can appear in the viral population within five passages, depending upon the size of the insert, nucleotide sequence, nature of the gene, and passage conditions. The utilization of these rCVBs in tissue culture and in vivo have clarified questions regarding viral tropism (Feuer, Pagarigan et al, 2005) (Puccini, Ruller et al, 2014), activation of the adaptive immune response against infection (Kemball, Harkins et al, 2009), mechanisms of virulence and disease (Zeng, Chen et al, 2013), and possible uses of CVB as therapeutic/vaccine vectors (Kim, Kim et al, 2012) (Miller, Geng et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of these novel myeloid cells was preceded by the induction of CCL12, a chemokine known to attract monocytic cells (Sarafi, Garcia-Zepeda et al, 1997) and fibrocytes (Moore, Murray et al, 2006). Although epithelial cells appeared spared from infection, CVB induced significant acute damage in the choroid plexus (Puccini, Ruller et al, 2014). Also, infected nestin + myeloid cells were shown to migrate into the CNS and assist in virus dissemination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation